Revitalisasi Harta Waris Islam (Faraid) Dalam Perekonomian - Ahmad Fatoni; Najmudin Najmudin (Syi`ar Iqtishadi : Journal of Islamic Economics, Finance and Banking, 2019)
Islamic inheritance laws or pharaids have played an important role in human sciences, especially the distribution of principled wealth to justice and responsibility. In addition, pharaids also have an important role in advancing the economy. This writing aims to analyze pharaids based on the Qur'an and hadith and their impact on the economy. This type of research is qualitative with the library research method. The results of the study show that the pharaids systematically ensured the redistribution of wealth by distributing wealth to each generation with predetermined parts, thus the Faraid had protected the rights of the heirs. Pharaid also supports the participation of women in economic activities, while allowing polygamy to support women's role and even bring a multiplier effect to the economy. Finally, with the existence of pharaids, the wealth produced by the deceased is again allocated to the factors of production through the economic cycle by each generation of heirs.